Pattern of admission and outcome of patients admitted to dedicated trauma intensive care unit (ticu), emergency department, teaching hospital, north-eastern malaysia (Bangladesh Journal of Medical Science, 2022)
Background: The role of dedicated Trauma ICU (TICU) in Emergency Department is vital in the chain of trauma care to ensure rehabilitation and sustainable critical care for a better survival outcome. This study is conducted to find out demographic patterns and predictors that can affect the outcomes of trauma patients.Methods: A retrospective review of all patients admitted to TICU, Hospital Universiti Sains Malaysia (HUSM) was carried out from January 1st, 2016 till December 31st, 2018. Data were collected from TICU admission and discharge registers and were analyse using SPSS version 23.0.Results: A total of 108 trauma patients were included in this study. All cases were exclusively blunt trauma (99.1%) and mainly attributed by road traffic injuries (92.6%). In terms of trauma clinical scoring, 25%(p= 0.001) presented with GCS score < 4, 46.9% (p=0.001) with RTS score 28had demonstrated prolonged ICU stay (> 7 days). Meanwhile 62.5% (p= 0.000) with GCS < 4, 75% (p= 0.000) with RTS < 5.5 and 75% (p= 0.000) with APACHE II > 28 were died in TICU. Besides that, those who had prolonged ICU stay (> 7 days) were 8.5 times higher odds to get sepsis (adj OR= 8.532; 95% CI: 2.710, 26.863; p= 0.000) and 7 times higher odds to get acute kidney injury (AKI) (adj OR= 7.131; 95% CI: 1.464, 34.733; p= 0.015). Meanwhile, patient who received blood transfusion led to 5 folds higher odds ofassociation with rhabdomyolysis (adj OR= 4.968; 95% CI: 1.821, 13.549; p= 0.002).Conclusion: In the midst of pandemic COVID-19 it is important for ED physician to early identify and prioritise high risk trauma patient based on predictors and allows for targeted monitoring and intervention that may improve their outcome and also optimise resources accordingly.Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 795-800